COMMON PRE-ANALYTICAL ERRORS IN BLOOD SAMPLE COLLECTION - Dina Fauziah; Anditri Weningtyas (STIKes Kepanjen, 2022)
The demand for an accurate laboratory examination is increasing. However, other than laboratory personnel, there still high number of medical staff that unaware of it. Even though they play very important role in the pre-analytic aspect of laboratory examination that is blood drawing. In this review, we elaborately explain common mishap in blood drawing practice and some component that need more attention when collecting blood for laboratory examination.